2021
DOI: 10.1371/journal.pgen.1009886
|View full text |Cite
|
Sign up to set email alerts
|

Targeted chromosomal Escherichia coli:dnaB exterior surface residues regulate DNA helicase behavior to maintain genomic stability and organismal fitness

Abstract: Helicase regulation involves modulation of unwinding speed to maintain coordination of DNA replication fork activities and is vital for replisome progression. Currently, mechanisms for helicase regulation that involve interactions with both DNA strands through a steric exclusion and wrapping (SEW) model and conformational shifts between dilated and constricted states have been examined in vitro. To better understand the mechanism and cellular impact of helicase regulation, we used CRISPR-Cas9 genome editing to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…The second annotated gene was dnaB, which encodes DNA polymerase III, the main enzyme responsible for DNA replication in bacteria. DNA replication is essential for bacterial growth and reproduction [41,42]. The third gene, betB, was reported to play an important role in the production of glycine betaine, which has been reported to act as an osmoprotectant protecting against abiotic stress conditions such as salinity [43,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second annotated gene was dnaB, which encodes DNA polymerase III, the main enzyme responsible for DNA replication in bacteria. DNA replication is essential for bacterial growth and reproduction [41,42]. The third gene, betB, was reported to play an important role in the production of glycine betaine, which has been reported to act as an osmoprotectant protecting against abiotic stress conditions such as salinity [43,48].…”
Section: Discussionmentioning
confidence: 99%
“…The second gene was dnaB, which encodes DNA polymerase III, the main enzyme responsible for DNA replication in bacteria. DNA replication is essential for bacterial growth and reproduction [41,42]. The betB gene plays an important role in the biosynthesis of the osmoprotectant glycine betaine.…”
Section: Comparative Genomic Analysis Of the Ten Chosen Bacillus Strainsmentioning
confidence: 99%
“…In addition, phages use the ribosomes of host bacteria to synthesize progeny phages. Development of cellular metabolism, DNA replication and repair, and protein synthesis are affected by NAD-dependent protein deacetylase, DNA helicase, D3 proteins, flap endonuclease, ribonucleotide reductase, and DNA polymerase I, etc ( Chim et al, 2018 ; Rozman Grinberg et al, 2018 ; Xu et al, 2018 ; Behrmann et al, 2021 ; Qureshi et al, 2021 ; Ren et al, 2021 ). Therefore, differences between the two phages in bacterial lysis, thermal stability and acid–base stability may be related to the proteins codified by gene 26 (NAD-dependent protein deacetylase of SIR2 family), gene 2 (flap endonuclease) and gene 28 (ribonucleotide reductase of class III anaerobic, large subunit) of phage CM_Kpn_HB132952, gene 50 (NAD-dependent protein deacetylase of SIR2 family), gene 30 (DNA helicase), gene 33 (DNA polymerase I), gene 43 (D3 protein), and gene 52 (ribonucleotide reductase of class III anaerobic, large subunit) of phage CM_Kpn_HB143742.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into sterically restricted, dilated, or constricted mutants revealed a direct link between conformation, rate of unwinding, and protein–protein interactions in vitro . Studies have also shown that both DNA strands contribute to unwinding, and a mechanism involving steric exclusion and wrapping (SEW) of the excluded ssDNA strand contributes to helicase regulation in vivo and in vitro ( 21–23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations of targeted mutations that disrupted helicase regulation led to proposal of a dual mechanism, wherein conformational changes in the helicase structure stimulated by protein–protein and protein–DNA interactions act as a molecular switch to conceal or expose the external residues for engagement with the excluded DNA strand ( 21 ). Upon loading onto ssDNA by DnaC or interaction with τ-CLC, the central channel of the DnaB hexamer constricts, making tighter and more productive contacts with the encircled strand for rapid unwinding ( 7 , 10 , 24 , 25 ) (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%